SISTEM TEMU KEMBALI INFORMASI PERUNDANG-UNDANGAN MENGGUNAKAN ALGORITMA TF-IDF (Information Technology and Telematics, 2014)
Abstract - Legislation in Indonesia is an important document that is widely accessible to the public. The need for information of this legislation led to the idea to make a search engine. System information contained in the current search engines are very many kinds, with the advantages and disadvantages of each system. This study designed an information retrieval system legislation applicable in Indonesia by using the TF-IDF algorithm. This method is used because it can display the retrieval results are sorted based on the weighting of the similarity between the query with the information on the document. This is done so that the user of a search engine that will be made, obtain data sequences from the highest similarity so that search becomes more efficient when compared to using a search engine that does not use query similarity with document sorting. Information retrieval is designed to facilitate the search for documents legislation in order to obtain information based on the highest weighting. Keywords: Information Retrieval, Legislation, TF-IDF Abstrak - Perundang-undangan di Indonesia merupakan dokumen penting yang banyak diakses oleh masyarakat. Kebutuhan akan informasi perundang-undangan ini memunculkan ide untuk membuat sebuah mesin pencari. Sistem informasi yang terdapat pada mesin pencari saat ini sangat banyak jenisnya, dengan kelebihan dan kekurangan di masing-masing sistem. Penelitian ini merancang sebuah sistem temu kembali informasi perundang-undangan yang berlaku di Indonesia dengan menggunakan algoritma TF-IDF. Aplikasi sistem ini dapat menampilkan hasil temu kembali secara terurut berdasarkan hasil pembobotan kemiripan antara query dengan informasi yang ada pada dokumen. Hal ini dilakukan agar pengguna dari mesin pencari yang akan dibuat, mendapatkan data yang terurut dari yang kemiripannya paling tinggi sehingga pencarian menjadi lebih efisien jika dibandingkan dengan menggunakan mesin pencari yang tidak menggunakan pengurutan kemiripan  query dengan dokumen. Sistem temu kembali informasi ini dibuat untuk mempermudah dalam pencarian dokumen perundang-undangan agar memperoleh informasi berdasarkan hasil pembobotan tertinggi.   Kata Kunci :  Sistem Temu  Kembali Informasi, Perundang-undangan, TF-IDF